Boşanmanın sonuçlarından maddi ve manevi tazminat - Kırmızı, Ali E. (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / Hukuk Anabilim Dalı, 2009)
Bu çalısmanın konusu, evlilik bosanma ile sonuçlandıgında tarafların birbirlerinden talep edecekleri maddi ve manevi tazminatın kosuları, bu tazminat miktarının belirlenmesinde dikkate alınacak hususlar, 4721 sayılı Medeni Kanunun getirdigi yenilikler, bu davalarda uygulanacak usul kuralları ve Yargıtay uygulamasının neler oldugudur. Bu çalısma giris, üç bölüm ve sonuç kısmından olusmaktadır. Giris bölümünde; genel olarak bosanmanın sonuçları, birinci bölümde; tazminat hukuku, ikinci bölümde; maddi tazminat taleplerinin maddi ve biçimsel kosulları, üçüncü bölümde; manevi tazminat taleplerinin maddi ve biçimsel kosulları, dördüncü bölümde, maddi ve manevi tazminat davalarındaki usul kuralları ve sonuç bölümünde ise, Yeni Medeni Kanunda maddi ve manevi tazminat ile ilgili degisiklikler incelenmistir.

The subject of the thesis to show, when the marriage is finished by consequence of divorce, conditons of claim for material and moral compansation by parties, matters that should be considered to determine amount of a compansaion, amendments which is brought by number of 4721 Civil Code, rules of procedures which must be applied in this cases and court of appeals practices. This thesis consist of three chapters, which are introduction, discussion and results. In the introduction chapter; generally divorce consequences, n the discussion; part 1 compansation law, in part 2; matarial and formal conditions of claim for material compensation, in part 3; material and formal conditions of claim for moral compensation, in part 4; lawrules of procedure in the material and moral compansation cases are discussed. In the final part or the results, analysis of amendments of matarial and moral compensation law in New Civil Code is summerised.
Material and moral compansation from divorce consequences
Keywords: Hukuk; Boşanmanın Sonuçları; Maddi Tazminat; Manevi Tazminat; Law; Consequences of Divorce; Material Compensation; Moral Compensation